Community-Based Sustainable Tourism Village through Nature and Culture Tourism - Rahmiati, Filda; Ismail, Yunita; Amin, Grace; Goenadhi, Felix; Chairy, Chairy (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
The decline in visitors during the COVID-19 outbreak is one of the factors affecting the profitability of tourist destinations. This condition is challenging for developing tourist villages, especially the Hegarmukti tourist village. Several activity restrictions during the COVID-19 outbreak have made community-based tourism development programs experience obstacles. Through this community service activity, the 4C model analysis (Conservation, Community, Culture, and Commerce) is to be applied to optimize the growth of the Hergarmukti tourist village. The activity begins with a semi-formal interview process and observations to gather information. Through this activity, it was revealed that some potential has not been exploited, especially in terms of natural and cultural tourism. Socialization activities by conducting capacity-building workshops for preserving natural ecosystems through waste management were conducted with the Situ Rawa Binong residents. Besides, cultural promotion activities through local art performances displayed by the Cahaya Gumilar Art Gallery also attract tourists. To run a sustainable tourism village, the community requires soft skills training in tourism and marketing. The study also offers several possible tourist attractions to stimulate the local economy.